Enhanced the Municipal Solid Waste Management in Kuala Lumpur by Implementing Technologies from European Countries: Strategies and Action Plans - Siti Fatimah, Che Osmi; Nadiah, Mokhtar; Noor Suraya, Romali; Siti Khadijah, Che Osmi (Penerbit UMP, 2013)
This paper has discusses theseveral action plan to improve municipal solid waste management (MSW) in Kuala Lumpur with the implementation of integrated MSW management from European countries. Several data of MSW management in Kuala Lumpur such as key legislation, population growth, solid waste generation, disposal and collection has been review and study for guidelines and evaluation of the best selection on MSW management for Kuala Lumpur. The main goal of this paper is to develop an effective MSW management, which can diminish the weakness of current MSW management in Kuala Lumpur. Based on the data gather, a combination of several MSW management and technologies from Europeancountries such as PAYT (Pay as You Throw) program, incinerator, Refused Derived Fuel (RDF) and Dual system has been found as the best selection for immediate and long term strategies for implementation on MSW managementin Kuala Lumpur.